PENGARUH CASH TURNOVER, NET INTEREST MARGIN, LOAN TO DEPOSIT RATIO, OPERATIONAL EFFECIENCY AND COST EFFECIENCY (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Toni Alvoro Kokoh; Clara Monica; Danu Panca Pragana; Mely Guslina Mariana Sinaga; Bayu Wulandari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The research objective is to test and analyze the effect of Cash Turnover, Net Interest Margin, Loan to Deposit Ratio, Operational Efficiency and Cost Efficiency (BOPO) on return on assets (ROA) in Conventional Banking Listed on the Indonesia Stock Exchange for the 2012-2016 period. This type of research is quantitative descriptive research. The nature of the research is explanatory research design. The research model is multiple linear regression. The results of this study are that Cash turnover has a significant and partially significant effect on return on assets (ROA) in Conventional Banking Listed on the Indonesia Stock Exchange for the 2012-2016 Period. Net Interest margin has a significant and partially significant effect on return on assets (ROA) in Conventional Banking Listed on the Indonesia Stock Exchange for the 2012-2016 period. The loan to deposit ratio has a significant and partial effect on return on assets (ROA) in Conventional Banking Registered on the Indonesia Stock Exchange for the 2012-2016 period. Operational Efficiency and Cost Efficiency (BOPO) has a partial and significant effect on return on assets (ROA) in Conventional Banking Registered on the Indonesia Stock Exchange for the 2012-2016 period. Cash Turnover, Net Interest Margin, Loan to Deposit Ratio, Operational Efficiency and Cost Efficiency (BOPO) have a significant and simultaneously significant effect on return on assets (ROA) in Conventional Banking Registered on the Indonesia Stock Exchange Period 2012-2016.